Comparative study of low dose of capecitabine versus standard dose in metastatic breast cancer: Efficacy and safety - Aboelnaga Engy M; El-beshbishi Wafaa (Forum of Clinical Oncology)
A lower dose of capecitabine revealed better toxicity profiles and comparable efficacy in treatment of metastatic breast cancer (MBC). We aimed to evaluate the efficacy and toxicity of lower dose of capecitabine in comparison with the standard dose.